Inovasi Pembelajaran dalam Memanfaatkan Teknologi Digital Aplikasi dan Platform E-Learning - Fitri Octaviani; Irwan Siagian (Journal on Education, 2024)
Technological advances have had a very rapid influence on the development of education in Indonesia. In the current era of the industrial revolution, technology can provide convenience in assisting the teaching and learning process, this is because technology-based learning media can make human work easier. Technology has become the main solution in providing more equitable access to education, bridging the gaps that exist between various regions and social groups. With advances in information and communication technology, education can now be accessed from anywhere and at any time, without being limited by geographic location. E-learning is a system or educational concept that utilizes information technology to support the learning process. Technology has great potential to create more equitable and inclusive access to education, enabling every individual to develop their potential to the fullest, regardless of their location or background. This research uses qualitative methods with library study techniques by reviewing various types of reading references to find conclusions regarding learning innovations in utilizing technology to improve the quality of education.